Faktor Pendorong Singapura Dalam Menandatangani Sri Lanka-Singapore Free Trade Agreement Pada Tahun 2018 - Candra Nadisa, Galuh Putu Rarasati; Kumala Dewi, Putu Ratih; Prameswari, A.A. Ayu Intan (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2020)
ABSTRACT This research is conducted with qualitative research method to compile the determinant factors of Singapore in signing a Free Trade Agreement with Sri Lanka.As a country with excellentfree economic sector, Singapore also has many FTAs. One of them is Sri Lanka-Singapore Free Trade Agreement with Sri Lanka in 2018. While Singapore is the second freest economy in the world, Sri Lanka is still transitioning from rural-based economy to urban, ranked in 111th place of the freest economy in the world, creating a clear gap between the countrywith Singapore. Singapore joining hands with Sri Lanka can be seen as one of Singapore's attempts on maximizing their economic and trade liberalization, in which the most effective way to trade liberalization is signing Free Trade Agreement. Every FTA that signed must have a determinant that make Singapore agree on signing the agreement, such as economic interests or other factors. Keywords: SLSFTA, Trade Liberalization, Free Trade Agreement.